Factors associated with the depression status of Chinese parents who have lost their only child - Ya-Ping Ye; Jing-Na Wang; Qing-Chun Li; Cai-Ming Xu; Chao Rong (Frontiers Media S.A., 2022)
AimThis study aimed to assess the risk factors for depression among parents who have lost their only child (PLOCs).MethodsWe used a cross-sectional survey to reveal the risk factors of depression among PLOCs. Multi-stage, stratified, cluster sampling was used to recruit the participants. The cluster sampling method was used to select PLOCs in Hangzhou, Zhejiang Province, and Wuhu, Anhui Province, while the stratified cluster sampling method was used in Anshun, Guizhou Province. A total of 651 PLOCs were recruited in this study. Participants completed the Social Support Rating Scale (SSRS) and the Geriatric Depression Scale-15 (GDS-15). Socio-demographics were also collected, including age, sex, monthly income, education level, marital status, self-reported health, and a number of diseases were collected as well. Chi-square tests and binary logistic regression were conducted to analyze the influence of these factors on PLOCs' mental status.ResultsTwo hundred and fifty-eight PLOCs (39.56%) reported depression. Compared to PLOCs living in Wuhu, those living in Hangzhou (OR = 3.374, CI = 2.337-4.870) had a higher risk of depression. Being single (OR = 1.449, CI = 1.019-2.061) and the presence/absence of grandchildren (OR = 0.430, CI = 0.274-0.676)were significantly associated with the depression status of PLOCs.ConclusionThe sampled Chinese PLOCs reported a high prevalence of depression that was influenced by their place of residence, marital status, and presence/absence of grandchildren. This may highlight the need for routine assessment and help of this group by the relevant stakeholders (including government, non-profit social organizations, and professional psychologists) with more attention paid to single and low-income PLOCs that have no grandchildren. It is imperative to build a comprehensive care system of "extended family-community-society-government" for this vulnerable group.